Irenaeus of Lyons - Osborn, Eric Francis (Cambridge ; New York : Cambridge University Press, 2001)
"Eric Osborn's book presents a major study of Irenaeus (125-200), bishop of Lyons, who attacked Gnostic theosophy with positive ideas as well as negative critiques. Irenaeus' combination of argument and imagery, logic and aesthetic, was directed to a new document, the Christian bible. Dominated by a Socratic love of truth and a classical love of beauty, he was a founder of western humanism. Erasmus, who edited the first printed edition of Irenaeus, praised him for his freshness and vigour. He is today valued for his splendid aphorisms, his optimism, love of the created world, evolutionary view of history, theology of beauty and humour."--Jacket
Cover; Half-title; Title; Copyright; Dedication; Contents; Preface; Abbreviations; CHAPTER 1 Irenaeus: argument and imagery; PART I Divine Intellect; PART II Economy; PART III Recapitulation; PART IV Participation; PART V Conclusion; Appendix: Gnosticism; Select bibliography; Citations from Irenaeus; Citations from the bible; Index of classical authors; Index of patristic authors; General index.
Includes bibliographical references (pages 275-289) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Irenaeus, -- Saint, Bishop of Lyon; Irénée, -- saint, -- environ 130-environ 202.; Irenaeus, -- Saint, Bishop of Lyon; Irenaeus -- Lugdunensis; Christian saints -- France -- Lyon -- Biography; Saints chrétiens -- Lyon (France) -- Biographies; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Christian saints; France -- Lyon; Teologi -- Teologi; Electronic books; Biographies; Biographies; Biographies